Public Perception of Large Scale Social Restrictions - Mohamad Audy Novaldi; Dasrun Hidayat (Universitas Muhammadiyah Jakarta, 2020)
This study focuses on the public perception of Soreang District, Bandung Regency regarding Large-Scale Social Restrictions. This problem is examined because in its implementation the Large Scale Social Restrictions creates many different perceptions that are felt by each individual, thus affecting the effectiveness of the implementation of the policy. The purpose of this study is to determine the extent of public knowledge and attitudes about Large Scale Social Restrictions and to find out whether the community has complied with the policy. To answer these objectives, researchers used descriptive research methods with a qualitative approach. The technique of collecting data through interviews, observation and document review. The interview involved most of the people of Soreang District, Bandung Regency. Meanwhile, document review is taken from news in various mass media as well as theory from relevant references. Data analysis techniques use reduction analysis, display, and data conclusion. The results of this study indicate that the people of Soreang District, Bandung Regency already understand and comply with the Large Scale Social Restrictions policy. This is supported by the results of interviews the researchers conducted with several informants, on average, with knowledge of the Large Scale Social Restrictions policy. This level of understanding is manifested through daily behavior by following the provisions of the Large Scale Social Restrictions and implementing health protocols.